Length heteroplasmy in the predominate mitochondrial DNA haplogroups in the Croatian population - Barbarić, Lucija, biologinja (Array, 2019)
Mitochondrial control region represents the most variable segment of the mitochondrial genome. The frequency and pattern of heteroplasmy has been described in several studies; however, none of the reports documented the Croatian population. In the present study, we screened the control region (1122 bp) of 95 individuals belonging to two predominant mitochondrial phylogenetic branches in the Croatian population, haplogroups H and U. Length heteroplasmy occurred in polycytosine (poly-C) tracts within three hypervariable segments of the control region with the following frequencies: HVSI - 26.3%, HVSII - 52.6% and HVSIII - 7.4%. Furthermore, the association between certain polymorphisms in HVSI and length heteroplasmy was investigated. Our results indicate that only polymorphisms located in the poly-C tract are associated with HVSI length heteroplasmy. The T to C transition at np 16189 is significantly associated with the occurrence of length heteroplasmy (p<0.0001). This effect was even stronger if the C insertion was present in the position 16193. The data support the hypothesis that an uninterrupted poly-C tract of more than eight cytosines leads to length heteroplasmy. Length heteroplasmy associated with the T to C substitution in np 16189 was predominantly found in haplogroup U.